Human polyomaviruses and other human viruses in neuroendocrine tumors - Schmitt, Markus; Höfler, Daniela; Koleganova, Nadezda; Pawlita, Michael (Cancer epidemiology, biomarkers & prevention, 2011)
Background: While the association of the Merkel cell polyomavirus (MCV) with the neuroendocrine Merkel cell carcinomas (MCC) has been shown recently, it is unknown whether other human polyomaviruses (HPyV) may be associated with neuroendocrine tumours (NETs) of distinct entities.Methods: Using novel, highly sensitive polyomavirus genotyping assays, we evaluated the prevalence of eight distinct HPyVs in a selection of 51 NETs from different entities. In addition, we analyzed these NETs for the presence of DNA from 12 adeno-associated virus (AAV) genotypes, adeno virus-5, 27 mucosal human papillomavirus (HPV) genotypes, hepatitis B (HBV), 8 human herpes viruses (HHV), and xenotropic murine leukemia virus-related virus (XMRV).Results: 43 of the 50 (86%) NETs were positive for the DNA integrity control. Of these, 2 of 3 MCCs (67%) were positive for MCV. NETs from other entities, however, were negative for all HPyVs. Only a small subset of lung and appendix NETs were positive for EBV, HHV-6, and -7.Conclusion: While the association of MCV with MCC was confirmed, other human viruses could not be identified as potentially causative agents of other NETs.Impact: Our findings suggest that the human viruses tested for in this study do not play a comparable role in NETs like the polyomavirus MCV in MCC. Cancer Epidemiol Biomarkers Prev; 20(7); 1558-61. ©2011 AACR.
Gesehen am 12.10.2022